1989
DOI: 10.1080/01652176.1989.9694209
|View full text |Cite
|
Sign up to set email alerts
|

N‐oxidation, O‐demethylation, and excretion of trimethoprim by the turtlePseudemys scripta elegans

Abstract: SUMMARY Trimethoprim was excreted within one hour after being given orally to the turtle Pseudemis scripta elegans. No 0-demethylated or N-oxide metabolites were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our first attempt to demonstrate the ability of Pseudemys scripta elegans for 0-demethylation reactions with the test compound trimethoprim was negative (21). This is in contrast with sulphadimethoxine, which is 0-dealkylated at the 2 and 6 positions, the 2 position being favoured for oxidative attack.…”
Section: Discussionmentioning
confidence: 84%
“…Our first attempt to demonstrate the ability of Pseudemys scripta elegans for 0-demethylation reactions with the test compound trimethoprim was negative (21). This is in contrast with sulphadimethoxine, which is 0-dealkylated at the 2 and 6 positions, the 2 position being favoured for oxidative attack.…”
Section: Discussionmentioning
confidence: 84%
“…Data about SMZ metabolism and renal excretion in pigs are scarce (6). With respect to trimethoprim (TMP), its metabolic pathways 0-demeth%lation or dealkylation, a-C-oxidation and N-oxidation are demonstrated in Figure 1 (4,7,11,16,18,19,23). Friis et al (4), Nielsen et al (7,8,10) and Nordholm and Dalgaard (11) demonstrated that the MI and M4 metabolites along with their glucuronide conjugates are the main metabolites in pigs' urine.…”
Section: Introductionmentioning
confidence: 99%
“…The N4-acetyl and hydroxy metabolite of sulphamethoxazole were synthesised by Dr. Vree as described (19). The protein binding and deglucuronidation of samples were carried out as described (12,13,14,23) and the calculation of pharmacokinetic parameters was performed according to standard procedures (1). Because no plasma concentration data of the M4 metabolite and the glucuronide conjugates of MI and M4 were available, the quantification limit of the extraction method (0.08 pg/m1) was used in the estimation of their renal clearance values…”
mentioning
confidence: 99%
“…Recently is was shown that the turtle Pseudemys scripta elegans is able to perform 0-dealkylation reactions on sulphadimethoxine and sulphamonomethoxine, but not on trimethoprim (9,10,11). In sulphamonomethoxine an 0-dealkylation reaction can only be carried out at the 6 position.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonamides with methoxy groups in the pyrimidine ring are eliminated slowly in man, e.g. the elimination half-life of sulphamethomidine (4-sulphanilamido-2-methy1-6-methoxypyrimidine) is 34 h, that of sulphamonomethoxine 32 h, sulphadimethoxine 32 h, and sulphadoxine 110 h (1, 6,8,9). The rate of elimination of this group of methoxy sulphonamides is more rapid in various other species such as in the cow, the horse, and the pig, with relatively short half-lives of about 10 h (2, 4, 5).…”
Section: Introductionmentioning
confidence: 99%